‘PERTUNJUKAN INDAH’ DALAM NOVEL CARRIE [‘Beautiful Performace’ in Novel Carrie] - Khoirul Muttaqin (Kantor Bahasa Provinsi Maluku, 2016)
The objective of this research is to describe the gathering of all kinds of writing styles in novel Carrie. In addition, this research also describes the setting of place that can be found in almost important events in the novel and the oddity experienced by the characters in the novel. The research method used descriptivequalitative with the approach that focuses on the intrinsic element of the novel that is analyzed by using carnivalistic concept. The result of the research showed that the novel could be categorized into carnivalistic novel because in the novel, there are varous kinds of writing styles that might not be fictional writing. In addition, the fact that the novel belongs to a carnivalistic novel was supported by the setting of place (general place) and the oddity experienced by its characters. In conclusion, the carnivalistic characteristics of the novel makes the novel expose such a “beautiful performance”.Penelitian ini bertujuan untuk mendeskripsikan mengenai berjejalnya segala jenis tulisan dalam novel Carrie. Selain itu,dideskripsikan pula adanya latar tempat di sebagian besar peristiwa penting di dalamnya, serta keanehan-keanehan yang dialami tokoh dalam cerpen tersebut. Metode penelitian yang dipakai adalah metode deskriptif-kualitatif dengan pendekatan yang berfokus pada unsur intrinsik novel yang dianalisis dengan konsep karnivalistik.Hasil penelitian ini adalah novel tersebut merupakan jenis novel karnivalistik karena di dalamnya terdapat berbagai macam jenis tulisan yang bisa saja tulisan tersebut bukan tergolong tulisan fiksional.Selain itu kekarnivalistikan novel tersebut didukung dengan adanya latar tempat (tempat umum) dan keanehan yang dialami tokohnya.Simpulanya, ciri kekarnivalistikan novel tersebut membuat novel tersebut seolah menampakkan “pertunjukan indah”.